Carbon dioxide (CO2) reforming of methane to syngas over NI/SBA-15 catalyst - Mohamad Irsyad, Othman (2014)
Global emissions of carbon dioxide (CO2) was the main cause of human-induced global warming which is increased by 1.1% at 34.5 billion tonnes in 2012. There are many ways to reduce CO2 product such as conversion of CO2 to fuel, utilization of CO2 as a chemicals feedstock and non-conversion use of CO2 utilization of CO2 for methane reforming to syngas will be studied over Ni/SBA-15. The SBA-15 and Ni/SBA-15 will be synthesized by conversional and impregnation method, respectively. The chemical and physical characteristics of the catalysts before and after catalytic test will be investigated using X-ray diffraction (XRD), Thermogravimetric Analysis (TGA), Transmission Electron Microscope (TEM) and Brunauer-Emmett–Teller, Autosorb-1, Quantachrome (BET). SBA-15 have their unique structural features like high surface area, uniform and well defined pore topology. Nickel (Ni) based catalysts are one of the excellent catalyst systems for the CO2 reforming to methane besides the noble metals catalysts. Ni/SBA-15 expected to exhibited excellent catalytic performance in terms of CO2 conversion and long-term stability. The activity of the catalysts correlated strongly with the surface area and active site of the materials. This expectations was due to advantages of good structural stability and unique pore structural properties of SBA-15 as catalyst support and good active site of Ni, make this Ni/SBA-15 catalyst is suitable to be used for CO2 reforming of methane. This expectation was due to the good structural stability and unique structural properties of SBA-15.